MATHEMATICAL MODELING OF TOTAL STARCH AND CRUDE FIBER IN PURPLE SWEET POTATO (IPOMOEA BATATAS) DURING THE TUBBER FILLING STAGE APPLIED WITH LIQUID ORGANIC FERTILIZER FROM GUINEA PIG WASTE (CAVIA PORCELLUS) - Aji, Hilmi
Purple sweet potato is classified as a functional local food crop rich in complex carbohydrates, especially starch and crude fiber which is suitable for people with type 2 diabetes mellitus. The age of the harvest that is too young or old results in decreased nutrition. Therefore, a mathematical model is needed that is used to predict total starch and crude fiber during growth. Purple sweet potato is widely cultivated in Indonesia. However, there are obstacles during the cultivation process is dependence on chemical fertilizers. One way that can be done is use guinea pig waste as a liquid organic fertilizer with a high N, P, and K content. The purpose of this study is to determine the total starch and crude fiber in purple sweet potato and their mathmeatical models during the tuber filling stage applied with liquid organic fertilizer from guinea pig waste. The research was condeucted from October 2021 to March 2022 at SITH ITB Education Garden, Haurngombong, Sumedang Regency, and Labtek 1A SITH ITB. Based on the results of the study, maximum total starch is 5.214,757 mg/plant in 119 days after planting formed gaussian mathematical model with equation f(x) = 4.518e(-(x-120,2)/24,91)^2), maximum total amylose is 1.747,598 mg/plant in 133 days after planting formed gompertz mathematical model with equation f(x) = 4,349x1012e(-28,23e^(-0,002x)), maximum total amylopectin is 4.124,323 mg/plant in 119 days after planting formed gaussian mathematical model with equation f(x) = 3.752e(-((x-119,2)/22,94)^2), and maximum total crude fiber is 100,745 mg/plant in 133 days after planting of formed gaussian mathematical model with equation f(x) = 239,2e(-((x-178,8)/50)^2). The results of this study are influenced by enviromental conditions, distribution of sugar in plants, formation of storage roots, and formation of secondary metabolites such as anthocyanins and beta-carotene.